A notation for problematic architecture interactions. - Davis, L. (Software engineering notes.)
The progression of component-based software engineering (CBSE) is essential to the rapid, cost-effective development of complex software systems. Given the choice of well-tested components, CBSE affords reusability and increases reliability. However, applications developed according to this practice can often suffer from difficult maintenance and control, problems that stem from improper or inadequate integrate solutions. Avoiding such unfortunate results requires knowledge of what causes the interoperability problems in the first place. The time for this assessment is during application design. In this paper, we define problematic architecture interactions using a simple notation with extendable properties. Furthermore, we delineate a multi-phase process for pre-integration analysis that relies on this notation. Through this effort, potential problematic architecture interactions can be illuminated and used to form the initial requirements of an integration architecture.